Study on Catalytic Activity and Kinetics of Urea-SCR Processes for NOx Removal from a Marine Diesel Exhaust Flow - Zhu, Yuanqing; Zhou, Song; Liu, Miao; Wang, Jinyu (Asian Journal of Chemistry, 2012)
NOx removal efficiencies (DeNOx rate) of marine urea-SCR systems are strongly depended on the catalyst activity and urea solution consumption rate, leading to a high installation and operation cost. For enhancing the DeNOx rate and reducing the urea consumption rate, catalytic activity and kinetics of urea-selective catalytic reduction (SCR) processes in the marine diesel exhaust systems are studied by employing computational fluid dynamics coupled with chemical reaction kinetics. In the paper, a 3-dimensional transient reaction model for a marine urea-SCR system is proposed. Based on the model, the catalytic processes of the urea-SCR system is studied and DeNOx rates and NH3-slips under different urea consumption rates are discussed. It is found that the calculated value of DeNOx rate is in good agreement with the measured value ca. 92.2 % at 5.3 gallons per hour of urea consumption rate. It is also provided that catalytic processes of urea-SCR systems can be predicted well with the model in the paper.